A parametric study of polymer-enhanced CO2 injection in a light-oil reservoir using full-physics simulation - Rapheephan Laochamroonvorapongse; Falan Srisuriyachai; Jirawat Chewaroungroaj (Journal of Petroleum Exploration and Production Technology)
Abstract This study aims to assess the performance of polymer-enhanced CO2 injection in a light-oil reservoir under various reservoir geometries, parameters, and polymer properties. We also introduce several injection techniques: Polymer-Alternating-Gas (PAG) injection and co-injection of CO2 with water/polymer. This study employs full-physics compositional and polymer simulation to construct mechanistic models to investigate the efficiency of each EOR method. The injection strategies are water, polymer, CO2, Water-Alternating-Gas (WAG), PAG, and co-injection of CO2 and water/polymer. These parametric studies focus on reservoir geometries (formation dip angle), reservoir properties (heterogeneity and permeability), polymer properties, WAG parameters, and CO2 miscibility. For a 20-meter reservoir without dipping, the co-injection of CO2 with polymer and PAG are shown to recover 10% and 8% more oil than WAG-CO2, respectively. Adding polymer helps minimize gravity segregation, leading to a more uniform miscible flood front and oil displacement. These injection techniques are promising even in reservoirs with vertical heterogeneity. For a reservoir with a 10° dip angle, CO2 injection from the updip location creates a stable flood front, yielding high oil recovery. The sensitivity analysis reveals that polymer properties such as concentration and permeability reduction factor must be high enough to stabilize the displacement flood front, but not so high as to hinder injectivity. From the study of miscibility level, PAG and co-injection of CO2 with polymer methods are effective at miscible conditions. The findings of this study help the initial screening of existing and new CO2-EOR injection techniques and the design of EOR injection in light oil reservoirs.